Effects of aerobic, anaerobic, and concurrent training on bone mineral density of rats - Castoldi, Robson Chacon; Louzada, Mario Jefferson Quirino [UNESP]; De Oliveira, Bruna Rezende Silva Martins [UNESP]; Ozaki, Guilherme Akio Tamura [UNESP]; Koike, Tatiana Emy [UNESP]; Garcia, Thiago Alves [UNESP]; Camargo, Regina Celi Trindade [UNESP]; Belangero, William Dias; Filho, José Carlos Silva Camargo [UNESP] (FapUNIFESP (SciELO), 2017)
A sample of 39 rats were divided into the following groups: baseline (BL); aerobic training (ET4 and ET8); anaerobic training (ST4 and ST8); and concurrent training (CT4 and CT8). The aerobic training was performed by swimming with a load corresponding to 70% of the anaerobic threshold; the anaerobic training was performed by jumping in water with a load corresponding to 50% of body weight; and the concurrent training combined the two protocols. The analysis of BMD was performed on the tibia of the animals and showed an increase in the density of the ST4, CT4, ET8, ST8, and CT8 groups when compared with both the BL and ET4. Thus, it is concluded that anaerobic exercise was shown to be effective in increasing the BMD of animals after four weeks of training; however, aerobic training was only able to raise BMD following eight weeks of training.
Keywords: Aerobic exercise; Bone density; Physical exercise